TANTANGAN DAN PELUANG EKONOMI KREATIF STUDI KASUS KAMPUNG KAOS MADINA - Nurintan Siregar (EKSYA : Jurnal Ekonomi Syariah, 2024)
The creative economy is an economic activity driven by creative industries that prioritizes the role of intellectual property. The creative industry itself is driven by entrepreneurs, namely people who have creative and innovative abilities. The aim of this research is to see what the challenges and opportunities are of the creative economy in the village of Kaos Madina. The research method used is a qualitative descriptive approach. The population and sample used were the owners and team of Madina T-shirt village through interviews and documentation and used secondary methods through previous research. The conclusion drawn from this research is that there are several opportunities and challenges faced by the Madina T-shirt village.